The Republic of Korea's economy in the swirl of global crisis - Dongchul Cho (Asian Development Bank Institute (ADBI), 2009)
This paper argues that the Republic of Korea (hereafter Korea) is not immune to global crises, but that a more than proportional response of gross domestic product to global crises does not seem to be the general case either. Along this line of reasoning, Korea's extreme response to the current crisis in the fourth quarter of 2008 was attributed not only to the crisis in the United States, but also to additional idiosyncratic components, such as the extraordinary collapse of the People's Republic of China's (PRC) imports and the drastic capital outflow from Korea. The paper also emphasizes the differences between the current recession and the currency crisis period. The currency crisis was mainly attributed to the internal fragility of Korea's financial market, but the current recession was caused mostly by external shocks. This difference was clearly reflected in the different responses of private consumption and exports, and hence employment. In the dimension of macroeconomic policy reactions, monetary policy was far more flexible this time than during the currency crisis period. From this analysis, two implications are drawn. First, as far as the economic response of the fourth quarter of 2008 being more extreme than necessary to rebalance the macroeconomic fundamentals in Korea, it is expected that those economic losses can be recovered relatively soon. Yet, for a more visible recovery of the Korean economy, the recovery of the PRC's domestic demand seems necessary, and a full-blown recovery will be in line with the global recovery. A second implication is that structural aspects are critical for maintaining economic stability as well as employing flexible macroeconomic policies. While the Korean economy plunged into a historic crisis in 1997 - triggered by the relatively small external shock of the Thai baht crisis - the economy is expected to remain relatively robust this time, even in the midst of the most serious global crisis since the Great Depression.
Keywords: E32; E44; F41; 330; Weltkonjunktur; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Vergleich; Währungskrise; Südkorea